Business Model Canvas Design As An Alternative Strategy On Coworking Space - et. al., Rosalin Samihardjo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The term Coworking Space is usually used for an office building that has the concept of offering a sharing area between one company and another to accommodate the company's business needs. Coworking Space users can come from startups (Start Up) to enterprise scale companies. The problem experienced by Coeorking Space is the lack of market penetration and the lack of information regarding coworking space in Indonesia, while the rate of economic growth is increasing rapidly, so there is a need for forms of spaces that can become centers of activity and interaction for cross-sector creative economy actors, both government and actors. business / industry, academics, as well as creative communities / forums. An alternative solution to solving these problems is to design a business model canvas that can be a strategy for the development of coworking spaces that can support the growth of the creative economy. The steps taken is to analyze the advantages and disadvantages of coworking space using SWOT analysis techniques, which are then mapped into nine blocks of the business model canvas.